The idea of economic development and the metaphor of the invisible hand. Remarks on the interpretation of Adam Smith’s legacy on the tercentenary of his birth - Wojciech Giza; Dariusz Grzybek (Ekonomista)
In the article, the research approach of the history of economic thought was used to present the idea of economic development in the context of the invisible hand mechanism. The structure of the study consists of three parts. In the first one, a justification for the advisability of applying the historical analysis method was presented in order to analyze the examined problem. Furthermore, the issue of economic development interpreted by A. Smith, was discussed. In the third part, the research showing how Smith’s successors interpret the market was undertaken and it was inquired into why we still consider ideas rooted in classical political economy to be an essential legacy of modern economics.